Chrysalis [compact disc, unabridged] : a thriller - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2022)
"Like millions of people around the world, Jeremy Logan (famed enigmalogist or investigator of unexplained things) has grown to rely on his incredible new tech device. Made by Chrysalis, the global multi-billion-dollar tech company, the small optical device connects people in a stunning new way, tapping into virtual reality for the first time on a wide scale. And yet, when Logan is summoned by Chrysalis to investigate a disturbing anomaly in the massive new product rollout, Logan is shocked to see the true scope of the massive company. He also quickly realizes that something in Chrysalis's technology is very wrong, and could be potentially devastating. The question is what, and where is the danger coming from?"--